SISTEM PAKAR DIAGNOSA PENYAKIT ANEMIA MENGGUNAKAN METODE CERTAINTY FACTOR DAN FORWARD CHAINING BERBASIS ANDROID - Denny Soggy Rachmad, Isnanda; Nilogiri, Agung; Yanuarti, Rosita (Lafadz Jaya Publisher, 2023)
Anemia is a disease related to the level of hemoglobin which is called red blood cells and causes a decrease in the level of oxygen that the body absorbs. Anemia is a disease that often occurs and occurs quite a lot in society. This study aims to determine the accuracy value of the certainty factor and forward chaining methods in an expert system for diagnosing anemia. This study designed an expert system by combining two methods, namely certainty factor and Android-based forward chaining. The use of the forward chaining method can make the system perform reasoning like an expert, then combine it with the certainty factor method with the aim that the system to be designed can measure the level of certainty of disease diagnosis. The results of this study are tests that have been carried out using 15 test data samples and produce a system accuracy value of 93.33%. Design using the certainty factor and forward chaining methods can work on expert systems in diagnosing anemia and shows the meaning that this system is feasible to use and is able to apply knowledge from experts to be able to diagnose anemia with a fairly accurate level.